Entrepreneurial Education and Self-employment: Does Entrepreneurial Self-efficacy Matter? - Moses Kisubi; Michael Korir; Ronald Bonuke (SEISENSE Business Review)
Purpose – The study sought to determine the mediating role of entrepreneurial self-efficacy in the relationship between entrepreneurship education and self-employment intentions.